THE EFFECT OF THE USE OF THE IPUSNAS (DIGITAL LIBRARY) APPLICATION ON STUDENTS' LITERACY ABILITIES AND LEARNING OUTCOMES IN THE ECONOMICS SUBJECT OF GRADE XI OF SMA NEGERI 8 KUPANG - Yosinta Hartati Luhur; Ari Data; Markus UK Yewang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research is motivated by the low literacy skills and learning outcomes of eleventh-grade students in economics at SMA Negeri 8 Kupang. The purpose of this study was to determine the effect of using the iPusnas application on literacy skills and learning outcomes in economics at SMA Negeri 8 Kupang. The method used in this study was quantitative with a survey approach. The overall study population consisted of 105 eleventh-grade students, from which a sample of 83 students was drawn using proportional random sampling. Data collection was conducted through observation, questionnaire distribution, and documentation. Data analysis was performed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software, which included testing the outer model and inner model. The results showed that using the iPusnas application had a positive and significant impact on literacy skills. Furthermore, literacy skills also have a positive and significant effect on learning outcomes. Furthermore, the use of the iPusnas application also has a positive and significant impact on learning outcomes. Thus, the use of the iPusnas application has been proven to significantly contribute to improving students' literacy skills and learning outcomes in Economics